By His Excellency Benning Wentworth, Esq ; ... A proclamation : Whereas His Majesty has been graciously pleased to order a number of troops, under the command of the Honourable Lieutenant-General St. Clair, to proceed from Great-Britain to Louisbourg ... Given at the Council-chamber in Portsmouth, the fifth day of June, 1746 . (Printed by Thomas Fleet., 1746)
Recruiting volunteers for service in Canada.